The Enigmatic Role of GBA2 in Controlling Locomotor Function - Woeste, Marina A.; Wachten, Dagmar (Frontiers in Molecular Neuroscience, 2017)
The non-lysosomal glucosylceramidase GBA2 catalyzes the hydrolysis of glucosylceramide to glucose and ceramide. Loss of GBA2 function results in accumulation of glucosylceramide. Mutations in the human GBA2 gene have been associated with hereditary spastic paraplegia (HSP) and autosomal-recessive cerebellar ataxia (ARCA). Patients suffering from these disorders exhibit impaired locomotion and neurological abnormalities. GBA2 mutations found in these patients have been proposed to impair GBA2 function. However, the molecular mechanism underlying the occurrence of mutations in the GBA2 gene and the development of locomotor dysfunction is not well understood. In this review, we aim to summarize recent findings regarding mutations in the GBA2 gene and their impact on GBA2 function in health and disease.